Individualized pelvic lymphadenectomy should follow neoadjuvant concurrent chemoradiotherapy for locally advanced cervical cancer. Issue 14 (April 2018) - Wei, Li-Chun; Li, Xin; Zhang, Ying; Dang, Yun-Zhi; Li, Wei-Wei; Li, Jian-Ping; Zhao, Li-Na; Liu, Shu-Juan; Li, Xia; Shi, Mei
Abstract : Abstract: To study the outcomes following concurrent chemoradiotherapy (CCRT) and subsequent radical surgery for locally advanced cervical cancer (LACC), analyze the relationship between imaging-diagnosed and postoperative-diagnosed lymph node (LN) involvement, and identify patients who would benefit from individualized pelvic lymphadenectomy. We retrospectively reviewed records of 410 patients who underwent CCRT followed by radical surgery for International Federation of Gynecology and Obstetrics Stage Ib2-IIIb disease. Correlations of LN size on imaging before CCRT with pathological responses after CCRT, overall survival (OS), distant metastasis-free survival (DMFS), and complications were analyzed. During a median follow-up of 51.3 months, the respective 5-year OS and DMFS were 86.7% and 88.6%, respectively. Pathological primary tumor type, LN size on imaging before CCRT, and pathologic response after CCRT were independent prognostic factors for OS. Patients with a LN ≥0.8 cm had a significantly higher residual carcinoma rate versus those with LN <0.8 cm (33% vs 22.6%, P = .032). Postoperative pathological positive LN frequencies differed significantly by LN size on imaging (LN <0.8 cm vs LN ≥0.8 cm, 3% vs 19.3%, P < .0001). Grade 1–3 lower extremity edema occurred in 23.9% of cases; no grade 3–4 gastrointestinal and genitourinary toxicities were observed. CCRT followed by radical surgery for LACC yielded encouraging outcomes without unacceptable complications. Additionally, patients with a LN <0.8 cm on imaging before CCRT had a very low risk of postoperative pathological positive LN identification. Individualized pelvic lymphadenectomy (e.g., omitting or limiting the extent of LN dissection) might be an alternative option for some patients with a low risk of LN metastasis.